Production of mixed matrix hollow fiber membrane for CO2/CH4 separation - Abdul Karim, Zulhairun (Elsevier, 2014)
Studies on mixed matrix membrane (MMM) have been sprouting rapidly since the last few decades, but mostly fabricated in the form of dense, flat films. In this work, hollow fiber Polysulfone (PSF)-Cloisite®15A (C15A) MMM were produced using our in-house hollow fiber spinning machine. Various spinning parameters are at play in order to ensure the formation of defect-free high performance hollow fiber. Spinning process parameters such as dry gap height, force convection rate, dope extrusion rate, and take-up speed have been systematically studied in order to identify the optimum fabrication conditions. Extensive characterizations on the membrane morphology, membrane surface properties, polymer d-spacing and gas separation performance were conducted using SEM, AFM, XRD, and pure gas permeation experiment. The appropriate balance between dry-gap residence time and force convective rate is essential to yield membrane with good permeability-selectivity combinations. CO2 permeance was increased from 17.39 to 56.25 × 10- 6 cm3 (STP)/cm2 s cmHg when the dope extrusion rate was increased from 1.5 cm3/min to the optimum extrusion rate of 2.5 cm3/min. Membranes spun at high collection speed (up to 35 m/min) exhibited practically attractive fiber geometry comparable to commercial hollow fibers (∼300 μm diameter) but the permeation properties were rather disappointing which might be caused by excessive deformation of polymer chain due to stretching. Hollow fiber MMM containing layered organoclay has exhibited excellent CO2/CH4 pure gas selectivity of 40.26%, 46% higher than that of pristine hollow fiber fabricated under the same optimized conditions without compromising the CO2 flux. The MMM was also found to be more thermally and mechanically robust in comparison to its neat counterpart.